(untitled) (Bangladesh Journal of Botany, 2026)
The Sal (Shorea robusta) forests of Bangladesh, particularly the Madhupur tract, are ecologically significant yet increasingly threatened by anthropogenic pressures and habitat fragmentation. This study was conducted in the Dokhola village adjacent to the Madhupur Sal Forest to evaluate the phytosociological structure and plant species diversity across four growth forms. Vegetation was sampled using a nested quadrat approach. Importance Value Index (IVI) was calculated for each species. A total of 83 plant species were recorded, comprising 44 trees, 16 shrubs, 11 herbs, and 12 climbers/lianas. Shorea robusta overwhelmingly dominated the tree stratum (IVI = 128.26), while Clerodendrum infortunatum dominated the shrub layer (IVI = 64.28). The herbaceous layer exhibited extreme suppression, with Ageratum conyzoides commanding 74% of the stratum (IVI = 222.35). Among climbers, Paederia foetida (IVI = 81.53) and Mikania micrantha (IVI = 54.21) were co-dominant. Questionnaire surveys revealed that 66% of local respondents depend on forest resources, contributing to diversity decline. Respondents recommended awareness campaigns, sustainable non-timber forest product harvesting, and exotic species control. This study provides baseline data urgently needed for conservation planning and sustainable management of Sal forests. Bangladesh J. Bot. 55(2): 257-268, 2026 (June)